Monetary Policy Analysis on the Interest Rate Value of Indonesian Bank : Case Study of the Impact of the Fed's Policy in 2022 - Afifah Damayanti; Muhammad Dwi Laksono; Esha Siti Khodimah; Evada Rustinah; Muhammad AlZidan Herdiansyah; Ahmad Setiawan Nuraya (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study examines the impact of Federal Reserve (Fed) monetary policy in 2022 on the Bank Indonesia (BI) benchmark interest rate and BI's responses to maintain national economic stability. In response to high inflation in the United States, the Fed raised interest rates aggressively from 0.25% to 4.25%. This policy resulted in the depreciation of the rupiah exchange rate, capital outflows, and an increase in imported inflation in Indonesia. In response, BI gradually increased the BI 7-Day Reverse Repo Rate from 3.50% to 5.75%, intervened in the foreign exchange (forex) market, and strengthened policy coordination with fiscal authorities. The results demonstrate that BI successfully maintained exchange rate stability and contained inflation. Economic growth remained positive at 5.72% year over year in the third quarter of 2022. These findings underscore the importance of adaptive, measured, and coordinated monetary policy in the face of global dynamics.